Screening of anti-nematode potential through inhibition of egg hatching in plant-parasitic nematode Meloidogyne javanica - Shakya, Shilpy; Yadav, Bindhya Chal (Current Botany, 2020)
Plant-parasitic nematodes have emerged as nature’s most successful among all parasites known till today. These animals have been reported from all terrains of all ecosystems. Their capability to survive on a wide diversity of the host plants, circumvent host plant defence is a few of several of their secrets making them most successful of all known parasites. Among various groups of plant-parasitic nematodes, endo-parasitic nematodes are the most damaging one and also difficult to control. Meloidogyne sps. are commonly known as root-knot nematodes. Our inability to control them is primarily due to our poor understanding of the biology of these plant parasites. Due to the availability of the complete genome sequence of few Meloidogyne species, biotechnological interventions are used to unravel the secrets of their success. Chemical controls of these nematodes are extensively reported in the literature. Due to the environmental toxicity associated with these chemicals, and restrictions on the use of chemicals against nematodes led to screening and development of eco-friendly management strategies. The present study was conducted to screen nematotoxic properties of Neem (Azadirachta indica), Jatropha (Jatropha curcas), Kachnar (Bauhinia variegate), Bel (Aegle marmelos) and Eucalyptus (Eucalyptus globules) leaf extracts against root-knot nematode Meloidogyne javanica in vitro. The aqueous extracts were used against the hatching of the nematode eggs, movement of second stage juveniles (J2) and the viability of the J2 in increasing concentration of the bioactive compound. The eggs were treated with various concentrations of the selected extracts for different time periods ranging from 24h to 6 days. A significant inhibition of egg hatching and increase in the mortality of the nematode juvenile in few of the aqueous extracts were recorded. Reduced egg hatching and increased mortality of the nematode juveniles could be maybe the indicators of the presence of anti-nematode potential in the selected plant leaves. The results from the study can pave the way for the development of eco-friendly management strategies for plant-parasitic nematodes.